2014
DOI: 10.1016/j.jvolgeores.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Permeability measurements of Campi Flegrei pyroclastic products: An example from the Campanian Ignimbrite and Monte Nuovo eruptions

Abstract: In order to understand outgassing during volcanic eruptions, we performed permeability measurements on trachy-phonolitic pyroclastic products from the Campanian Ignimbrite and Monte Nuovo, two explosive eruptions from the active Campi Flegrei caldera, Southern Italy. Viscous (Darcian) permeability spans a wide range between 1.22 × 10 −14 and 9.31 × 10 −11 m 2 . Inertial (non-Darcian) permeability follows the same trend as viscous permeability: it increases as viscous permeability increases, highlighting the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…A comparison of k 1 and k 2 yields a power-law trend that is similar to those found in previous experimental and natural studies (Fig. 4) (Rust and Cashman, 2004;Wright et al, 2007;Takeuchi et al, 2009;Polacci et al, 2014). Interestingly, the experimental samples span most of the k 1 /k 2 range covered by the natural samples.…”
Section: Experimental Permeabilitiessupporting
confidence: 85%
“…A comparison of k 1 and k 2 yields a power-law trend that is similar to those found in previous experimental and natural studies (Fig. 4) (Rust and Cashman, 2004;Wright et al, 2007;Takeuchi et al, 2009;Polacci et al, 2014). Interestingly, the experimental samples span most of the k 1 /k 2 range covered by the natural samples.…”
Section: Experimental Permeabilitiessupporting
confidence: 85%
“…The combined effects of crystal and vesicle textures on magma rheology and their relationship to eruptive style and intensity is a very active field of investigation. It has long been established that viscosity, the most important rheological property governing magma transport processes, is a function of magma composition, temperature, volatile content, crystal content, size, shape, distribution and orientation 2 , 3 and vesicle content and arrangement 4 , 5 . Recently, earth scientists have shown that crystal shapes, besides their abundances, have a strong effect on magma rheological response 3 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Textural measurements on samples Textural data provide information on magma pressure and thermal histories in conduits and plumes. For example, vesicle number densities (VNDs; i.e., the number of vesicles per unit bulk volume) provide estimates of magma decompression rates [Toramaru 2006, Shea et al 2011, Wright et al 2012b] and eruption intensities Cashman 2011, Alfano et al 2012], while crystal size distributions (CSDs) and vesicle size distributions (VSDs) (i.e., the number of crystals or vesicles in each size class per unit bulk volume) provide information on crystallization and differentiation in magma reservoirs and conduits [Fornaciai et al 2009, Shea et al 2009, Brugger and Hammer 2010, Arzilli and Carroll 2013, and on magma vesiculation [Bai et al 2008, Gurioli et al 2008, Colò et al 2010, Shea et al 2010, Carey et al 2012, permeability [Mueller et al 2008, Bouvet de Maissoneuve et al 2009, Polacci et al 2014, Heap et al 2014, Kendrick et al 2016, Colombier et al 2017, and degassing/outgassing [Burton et al 2007, Degruyter et al 2010a, 2012. Furthermore, VSDs, CSDs, melt chemistry and volatile content feed into magma rheology estimates [Mader et al 2013, Vona et al 2013.…”
Section: From Magma Ascentmentioning
confidence: 99%
“…As an example, we report here a list of recent works which, embracing different techniques, have provided improvements in the following research fields: analytical [Metrich and Wallace 2008, Bachmann et al 2010, Blundy et al 2010, Mercier et al 2010, Metrich et al 2010, Edmonds et al 2013, experimental [Kueppers et al 2006, Ardia et al 2008Giordano et al 2008, Lavallée et al 2007, Caricchi et al 2011, Cimarelli et al 2011, Llewellin et al 2011, Martel 2012, Okumura et al 2013, Rivalta et al 2013, Polacci et al 2014, Kendrick et al 2014a, Wadsworth et al, 2014, Kendrick et al 2016, Kolzenburg et al 2016a, b, Russell and Giordano 2016Del Bello et al 2017], numerical [Costa et al 2007a, Maccaferri et al 2010, Longo et al 2012, de' Michieli Vitturi et al 2013, Melnik and Costa 2014 and observational volcanology [Kueppers et al 2005, Gurioli et al 2008, Andronico et al 2009, Gudmunsson et al 2012, Cashman et al 2013, Tuffen et al 2013, Gaudin et al 2016, volcano geophysics [Wright et al 2012a, Harris 2013, Ripepe et al 2013…”
Section: Introductionmentioning
confidence: 99%